KETEPATAN WAKTU PELAPORAN KEUANGAN PADA MASA PANDEMI COVID-19 (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR DIBURSA EFEK INDONESIA) - Muhammad Rizal Hasibuan (Universitas Negeri Medan (UNIMED), 2023)
The research problem is whether the complexity of company operations (X1),auditcommittee(X2),managerialownership(X3),andpublicownership(X4)affectthetimeliness of financial reporting (Y). The purpose of this research is to examine theeffectofthecomplexityofcompanyoperations,auditcommittees,managerialownershipandpublicownershiponthetimelinessoffinancialreportinginmanufacturingcompanies before and during the Covid 19 pandemic.TheresearchpopulationformanufacturingcompanieslistedontheIDXforthe2018-2021 period is 166 companies. The sampling method used purposive samplingmethod,obtained103samplecompaniesfor4yearsofobservationwith412observations, obtained from audited annual reports, samples taken from the websitewww.idx.co.id.DataanalysistechniquesuseddescriptivestatisticsandLogisticRegressionAnalysis with the SPSS 25 test tool.TheresultsoftheresearchpartiallybeforeandduringthepandemicX1andX3had an effect on the Timeliness of Financial Reporting, while X2 and X4 had no effecton the Timeliness of Financial Reporting. Simultaneously X1, X2, X3, and X4 affect theTimeliness of Financial Reporting before and during the pandemic. Then there is adifference in X1 before and during the pandemic, and there is no difference in Y, X2,X3and X4. before and during the pandemic.The research results are in line with Afriyeni & Doni (2019), Didi Gusriadi(2020) but not in line with Prasetyo & Sari (2019) and Emil Lia Majid (2022). Theresearchresultssupportsignalingtheoryandagencytheory,wherethelevelofcomplexityofcompanyoperations,auditcommittees,managerialownershipandpublic ownership will affect the timeliness of financial reporting and provide a signalforexternal parties in making decisions.